"Regardless, you are not the first woman": an illustrative case study of contextual risk factors impacting sexual and reproductive health and rights in Nicaragua - Samantha M. Luffy; Dabney P. Evans; Roger W. Rochat (BMC, 2019)
Abstract Background Rape, unintended pregnancy, and abortion are among the most controversial and stigmatized topics facing sexual and reproductive health researchers, advocates, and the public today. Over the past three decades, public health practicioners and human rights advocates have made great strides to advance our understanding of sexual and reproductive rights and how they should be protected. The overall aim of the study was to understand young women's personal experiences of unintended pregnancy in the context of Nicaragua's repressive legal and sociocultural landscape. Ten in-depth interviews (IDIs) were conducted with women ages 16-23 in a city in North Central Nicaragua, from June to July 2014. Case presentation This case study focuses on the story of a 19-year-old Nicaraguan woman who was raped, became pregnant, and almost died from complications resulting from an unsafe abortion. Her case, detailed under the pseudonym Ana Maria, presents unique challenges related to the fulfillment of sexual and reproductive rights due to the restrictive social norms related to sexual health, ubiquitous violence against women (VAW) and the total ban on abortion in Nicaragua. The case also provides a useful lens through which to examine individual sexual and reproductive health (SRH) experiences, particularly those of rape, unintended pregnancy, and unsafe abortion; this in-depth analysis identifies the contextual risk factors that contributed to Ana Maria's experience. Conclusions Far too many women experience their sexuality in the context of individual and structural violence. Ana Maria's case provides several important lessons for the realization of sexual and reproductive health and rights in countries with restrictive legal policies and conservative cultural norms around sexuality. Ana Maria's experience demonstrates that an individual's health decisions are not made in isolation, free from the influence of social norms and national laws. We present an overview of the key risk and contextual factors that contributed to Ana Maria's experience of violence, unintended pregnancy, and unsafe abortion.